Low preoperative psoas muscle mass index is a risk factor for distal cholangiocarcinoma recurrence after pancreatoduodenectomy: a retrospective analysis - Saori Umezawa; Shinjiro Kobayashi; Takehito Otsubo (World Journal of Surgical Oncology, 2022)
Abstract Background This study aimed to investigate whether preoperative muscle mass is associated with the recurrence of distal cholangiocarcinoma after pancreatoduodenectomy (PD). Methods We retrospectively examined 88 patients who had undergone PD for distal cholangiocarcinoma. The preoperative psoas muscle mass index (PMI) was measured using computed tomography as an index of muscle mass. We performed multivariate analysis of factors influencing early recurrence and developed a prognostic survival model using independent risk factors for recurrence. Results The cut-off PMI values for recurrence within 1 year of surgery, determined from the receiver operating characteristic curve, were 5.90 cm2/m2 in males and 3.98 cm2/m2 in females. Multivariate analysis of effects associated with early recurrence within 1 year indicated that low PMI (odds ratio [OR] 9.322; 95% confidence interval [CI] 2.832 − 30.678; p = 0.0002) and lymph node metastasis (OR 5.474; 95% CI 1.620 − 18.497; p = 0.0062) were independent risk factors, and the median recurrence-free survival (RFS) of the low and high PMI groups were 21.6 and 81.0 months, respectively (p = 0.0214). The median RFS for zero, one, and two risk factors of low PMI and lymph node metastasis were as follows: zero variables, median not reached; one variable, 15.3 months; two variables: 6 months. Conclusions Low preoperative PMI may be a risk factor for distal cholangiocarcinoma recurrence after PD. Trial registration The Institutional Review Board of St. Marianna University School of Medicine approved this study prior to commencement of data collection and analysis on October 9, 2020 (IRB no. 5006) and waived the informed consent requirement.